Isolation of Escherichia coli from various organs of broiler chickens with complicated chronic respiratory disease - Zainal Abidin, Nurul Syuhada; Bejo, Mohd Hair; Abdul Rahman, Omar; Bejo, Siti Khairani; Zakaria, Zunita (Faculty of Veterinary Medicine, Universiti Putra Malaysia, 2013)
Escherichia coli was isolated from broiler chickens in 17 farms in the state of Johor (6 farms), Melaka (6 farms) and Perak (5 farms), Malaysia with clinical signs and lesions of complicated chronic respiratory disease (CCRD). The affected live chickens which showed clinical signs of distended abdomen, respiratory distress, weak, stunted and ruffled feather, whilst the dead chicken with distended abdomen were selected in the study. Upon necropsy, pericarditis, air sacculitis, perihepatitis, ascites, splenitis and peritonitis were the common lesions recorded. Samples of heart, liver, spleen, air sac and peritoneal swab were collected for E. coli isolation and identification. E. coli was isolated from 40% (2/5), 67% (4/6) and 60% (3/5) farms in Johor, Melaka and Perak, respectively. Heart (26%) and spleen (26%) were the common samples positive for E. coli followed by the liver (22%), air sacs (17%) and peritoneal swabs (9%).